Attitude Control System for Flight: A Comprehensive Review - Muhammed Faisal I.; Nasiya N. (International Journal of Solid State Innovations & Research, 2024)
Attitude control systems is an integral part of flight control systems because they are responsible for the stability and maneuverability of different airborne vehicles within all flight regimes. The following paper presents an extensive overview of attitude control systems that are commonly in use in various flight applications and examines their design implementation, and performance on the space. The paper starts with a general overview of the main mechanisms of attitude control followed by a classification of attitude control strategies which can broadly be categorized into open-loop and closed-loop systems. Also, this paper scrutinizes the evolution of attitude control systems from the mechanical actuators of the past to the modern fly-by-wire and autonomous control systems. This advancement is due to the new sensor technology, the increasing computing power, and the improved control algorithms that have facilitated better performance and reliability. Keys factors that have an effect on the choice of an architecture of control, including dynamic of the vehicle, mission requirements, and the condition of environment, are dealt with specifically. By the same, the review tackles the problems related to attitude control and proposes techniques like robust control techniques, adaptive control algorithms, and fault-tolerant mechanisms. This further considers how attitude control is integrated into navigation and guidance systems for the sake of maximum performance of flight and mission objectives.
Keywords: Aircraft; attitude control; backstepping controller; inertial measurement unit; tailsitter